Epidemiology of injuries in UK based golfers: a retrospective study - Williams, A.; Murray, A.; Sorbie, G. G. (The Physician and Sportsmedicine, 2024)
Objectives Golf participation numbers have increased in recent years within the UK and globally. A recent systematic review and meta-analysis of injuries in amateur and professional golfers showed over half of golfers sustain an injury during their lifetime. This review recommended that future research should utilize the recent international consensus on reporting of injury in golf. The aim of this study was to determine the frequency and severity of injuries sustained by UK-based golfers in the previous year.